Airway Epithelial miRNA Expression Is Altered in Asthma - Solberg, Owen D. (American Thoracic Society, 2012)
Rationale: Changes in airway epithelial cell differentiation, driven in part by IL-13, are important in asthma. Micro-RNAs (miRNAs) regulate cell differentiation in many systems and could contribute to epithelial abnormalities in asthma. Objectives: To determine whether airway epithelial miRNA expression is altered in asthma and identify IL-13–regulated miRNAs. Methods: We used miRNA microarrays to analyze bronchial epithelial brushings from 16 steroid-naive subjects with asthma before and after inhaled corticosteroids, 19 steroid-using subjects with asthma, and 12 healthy control subjects, and the effects of IL-13 and corticosteroids on cultured bronchial epithelial cells. We used quantitative polymerase chain reaction to confirm selected microarray results. Measurements and Main Results: Most (12 of 16) steroid-naive subjects with asthma had a markedly abnormal pattern of bronchial epithelial miRNA expression by microarray analysis. Compared with control subjects, 217 miRNAs were differentially expressed in steroid-naive subjects with asthma and 200 in steroid-using subjects with asthma (false discovery rate < 0.05). Treatment with inhaled corticosteroids had modest effects on miRNA expression in steroid-naive asthma, inducing a statistically significant (false discovery rate < 0.05) change for only nine miRNAs. qPCR analysis confirmed differential expression of 22 miRNAs that were highly differentially expressed by microarrays. IL-13 stimulation recapitulated changes in many differentially expressed miRNAs, including four members of the miR-34/449 family, and these changes in miR-34/449 family members were resistant to corticosteroids. Conclusions: Dramatic alterations of airway epithelial cell miRNA levels are a common feature of asthma. These alterations are only modestly corrected by inhaled corticosteroids. IL-13 effects may account for some of these alterations, including repression of miR-34/449 family members that have established roles in airway epithelial cell differentiation. Clinical trial registered with www.clinicaltrials.gov (NCT 00595153).